Methods Of Fixation Of Removable Dentures Using Dental Implants - Jaloliddinova, Shakhlo Jamolidinovna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This paper presents a review of modern methods for fixing complete removable dentures using dental implants. The main types of implant-retained systems are discussed, including ball attachments, bar constructions, telescopic and magnetic retainers, along with their clinical indications and functional features. It is shown that the use of dental implants significantly improves the stability of prostheses, ensures even load distribution, reduces alveolar ridge resorption, and enhances patients’ quality of life. Special attention is paid to the role of digital technologies (CAD/CAM design, 3D planning, milled suprastructures) in achieving precision and individualization of prosthetic constructions. Promising directions for further development include the use of mini-implants, nanostructured coatings, and biocompatible materials to increase the longevity and predictability of fixation systems.